Scale, colonisation and adapting to climate change: Insights from the Arabana people, South Australia. Issue 114 (August 2020) - Nursey-Bray, Melissa; Palmer, Robert; Stuart, Aaron; Arbon, Veronica; Rigney, Lester-Irabinna
Highlights: Knowledge is an important tool for Indigenous peoples to adapt to climate change. The Arabana people, South Australia articulate alternatives to Western climate discourses. Historical (colonial) Indigenous knowledge is as important as millennia old knowledge. Climate knowledge is observed at multiple scales and reflects history of colonial dispersal. Arabana adaptation to climate change is articulated as survival, agency and healing. Abstract: The role of knowledge in assisting Indigenous people adapt to climate change has been gaining increasing attention and local studies provide rich insights into how and where knowledge is used. This paper reports on the results of a qualitative cross-cultural research collaboration about climate change adaptation for the Arabana, an Indigenous people from South Australia. We find that the Arabana people have a corpus of observed historical knowledge of climate change, forged through a sustained period of colonial invasion, that offers fine level detail about likely climate impacts that is not captured by regional scientific projections. This knowledge includes actual observations about recent climate variability, as well as changes to flora, fauna, land and cultural sites. This historical knowledge about and observation of the environment is as important to the Arabana people as ancestral traditional knowledge for informing the contemporary climate change policy that affects them and their surroundings. Arabana knowledge sets about climate change and its impacts were also found to be intimately interconnected with other regional socio-economic activities (such as pastoralism and mining) which are the legacy of colonisation, and cannot be divorced from cultural perceptions and discussions about climate impacts. We conclude that in order to forge appropriate responses to the impacts of climate change, dialogues between policy makers and the Arabana needs to acknowledge the legitimacy of all Arabana knowledge, particularly historical knowledge that has been grafted through colonial dispossession.